Analysis Of Activity Based Costing And Cost Volume Profit To Determine Optimal Profit At The Eka Jaya Opak Factory - Zainab Khoiriyah; Nurwani; Laylan Syafina (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Competition in the traditional food industry requires Micro, Small, and Medium Enterprises (MSMEs) to have an accurate costing system to support optimal selling price determination and profit planning. The Eka Jaya Opak Factory, one of the MSMEs processing raw opak in Deli Serdang Regency, still uses conventional costing methods that only calculate raw material and direct labor costs, while factory overhead costs have not been allocated systematically. This condition has the potential to cause cost distortion and inaccuracies in profit planning. This study aims to analyze the application of Activity-Based Costing (ABC) in determining the cost of production and integrate it with Cost-Volume-Profit (CVP) analysis to determine optimal profit. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. Data are analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that the cost of production based on the ABC method is Rp 7,050.3/kg, higher than the conventional method of Rp 6,681/kg because overhead costs are allocated based on actual activities that consume resources. The integration of ABC and CVP resulted in an optimal selling price strategy at a 50% markup with a profit of Rp 109,984,664 per month, a Break Even Point of 6,394 kg, and a Margin of Safety of 79.5%. These findings indicate that the integrated ABC and CVP approach can improve the accuracy of cost information and support managerial decision-making in MSME profit planning more effectively and sustainably.